2021
DOI: 10.2478/ahem-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

The role of Helicobacter cinaedi in the development of atherosclerosis

Abstract: Helicobacter cinaedi (H. cinaedi) is a Gram-negative curved motile rod that causes bloodstream or enteric infections. It was suggested that H. cinaedi was involved in the progression of atherosclerosis. We aimed to investigate the presence of H. cinaedi DNA using a nested-polymerase chain reaction (PCR) in atheroma plaques from patients with atherosclerosis-induced vascular diseases. A total of 129 patients diagnosed with valvular heart disease due to atherosclerosis and 146 patients with non-atherosclerotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…If H. cinaedi does play an important role in the development of atherosclerosis and subsequent severe CVD, it may be possible to develop preventive therapies directed against this bacterium and potentially significantly improve the development of therapies for CVD. Unfortunately, to date, a small number of studies on the association of H. cinaedi with atherosclerosis are known ( Khan et al, 2014 ; Sarp et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If H. cinaedi does play an important role in the development of atherosclerosis and subsequent severe CVD, it may be possible to develop preventive therapies directed against this bacterium and potentially significantly improve the development of therapies for CVD. Unfortunately, to date, a small number of studies on the association of H. cinaedi with atherosclerosis are known ( Khan et al, 2014 ; Sarp et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A control group of 146 patients with non-atherosclerotic post-stenotic dilatation also participated in the study. Helicobacter cinaedi DNA was detected only in the group of patients with atherosclerosis, in six samples out of 129 ( Sarp et al, 2021 ). Statistical analysis showed that in this study, the presence of H. cinaedi was not an independent variable for the risk of atherosclerosis.…”
Section: Association Of the Bacterium Helicobacter Cinaedi ...mentioning
confidence: 99%